High levels of genetic variability and differentiation in hilsa shad, Tenualosa ilisha (Clupeidae, Clupeiformes) populations revealed by PCR-RFLP analysis of the mitochondrial DNA D-loop region - Mazumder,Sabuj Kanti (2009)
The hilsa shad, Tenualosa ilisha (Clupeidae, Clupeiformes) is an important anadromous clupeid species from the Western division of the Indo-Pacific region. It constitutes the largest single fishable species in Bangladesh. Information on genetic variability and population structure is very important for both management and conservation purposes. Past reports on the population structure of T. ilisha involving morphometric, allozyme and RAPD analyses are contradictory. We examined genetic variability and divergence in two riverine (the Jamuna and the Meghna), two estuarine (Kuakata and Sundarbans) and one marine (Cox's Bazar) populations of T. ilisha by applying PCR-RFLP analysis of the mtDNA D-loop region. The amplified PCR products were restricted with four restriction enzymes namely, XbaI, EcoRI, EcoRV, and HaeIII. High levels of haplotype and gene diversity within and significant differentiations among, populations of T. ilisha were observed in this study. Significant F ST values indicated differentiation among the river, estuary and marine populations. The UPGMA dendrogram based on genetic distance resulted in two major clusters, although, these were subsequently divided into three, corresponding to the riverine, estuarine and marine populations. The study underlines the usefulness of RFLP of mtDNA D-loop region as molecular markers, and detected at least two differentiated populations of T. ilisha in Bangladesh waters.